Ros Bandt interviewed by Belinda Webster in the Esso Performing Arts collection - Bandt, Ros (Rosalie); Webster, Belinda; Potter, Michelle, 1944-; National Library of Australia; Esso Australia; Esso Performing Arts and Oral History Archive Project (1989)
Bandt speaks of her musical education; childhood and family interest in music; university experiences and influences; her experiments and work at university; research in America; interest in music sculpture; her experiences in Europe and interest in early music; major sound influences and inspirations in her music; influences of the environment in her music; the importance of visuals and the performance environment; instruments she has made; her glass music; recordings; importance of space; philosophies on music; technology and computers; current work and themes at time of interview; minimalist music; Australian composers.
Part of a collection of oral history interviews produced by the Esso Performing Arts and Oral History Archive Project, funded by Esso Australia at the National Library of Australia. Project co-ordinated by Michelle Potter Esso Research Fellow in the Performing Arts at the National Library of Australia.
Recorded in Sydney on April 20 and 21, 1989.
Digital master available
Transcript available (86 p.)
Keywords: Bandt, Ros -- Interviews; Composers -- Australia -- Biography; Composers -- Australia -- Interviews